Use of Social Media for Strategies to Improve the Indonesian Economy for the Sustainability of MSMES - Rofif Satria Azraputra; Maryani Maryani; Erwin Halim (Bina Nusantara University, 2020)
Indonesia is currently entering the phase of this demographic bonus that must be used well. In the process of advancing micro, small and medium economic development, many Indonesians become small entrepreneurs selling products to others. The proportion of young people exceeds 25% of Indonesia's total population of around 250 million, plus 59.2 million Micro, Small and Medium Enterprises (MSMEs) units, contributing 61.41% of GDP. Indonesia is Indonesia's two main economic powers. However, even though the January 2016 data shows that the potential for Information and Communication Technology (ICT) infrastructure has reached around 90% of the population, and the mobile penetration rate of internet users exceeds 126%, there are still 90% of MSMEs. The unit is still running in the offline domain. Reaching 51.8% of the total population of Indonesia. Although he can only hold information technology by hand, one of them is through social media. You can take advantage of social media such as Facebook, Instagram, and Twitter to sell goods. E-UMKM is an Android-based application designed to sell Indonesian MSME products online and has been integrated with the system. The steps that must be taken include data collection, MSME product certification, application development, socialization and delivery systems. This activity is expected to help MSME business players in selling their businesses online through social media.